Aberrant DNA methylation profiles of inherited and sporadic colorectal cancer. Issue 1 (December 2015) - Sahnane, Nora; Magnoli, Francesca; Bernasconi, Barbara; Tibiletti, Maria; Romualdi, Chiara; Pedroni, Monica; Ponz de Leon, Maurizio; Magnani, Giulia; Reggiani-Bonetti, Luca; Bertario, Lucio; Signoroni, Stefano; Capella, Carlo; et al.
Abstract Background Aberrant DNA methylation has been widely investigated in sporadic colorectal carcinomas (CRCs), and extensive work has been performed to characterize different methylation profiles of CRC. Less information is available about the role of epigenetics in hereditary CRC and about the possible clinical use of epigenetic biomarkers in CRC, regardless of the etiopathogenesis. Long interspersed nucleotide element 1 (LINE-1) hypomethylation and gene-specific hypermethylation of 38 promoters were analyzed in multicenter series of 220 CRCs including 71 Lynch (Lynch colorectal cancer with microsatellite instability (LS-MSI)), 23 CRCs of patients under 40 years in which the main inherited CRC syndromes had been excluded (early-onset colorectal cancer with microsatellite stability (EO-MSS)), and 126 sporadic CRCs, comprising 28 cases with microsatellite instability (S-MSI) and 98 that were microsatellite stable (S-MSS). All tumor methylation patterns were integrated with clinico-pathological and genetic characteristics, namely chromosomal instability (CIN), TP53 loss, BRAF, andKRAS mutations. Results LS-MSI mainly showed absence of extensive DNA hypo- and hypermethylation. LINE-1 hypomethylation was observed in a subset of LS-MSI that were associated with the worse prognosis. Genetically, they commonly displayed G:A transition in theKRAS gene and absence of a CIN phenotype and ofTP53 loss. S-MSI exhibited a specific epigenetic profile showing low rates of LINE-1 hypomethylation and extensive gene hypermethylation. S-MSI were mainly characterized byMLH1 methylation, BRA F mutation, and absence of a CIN phenotype and of TP53 loss. By contrast, S-MSS showed a high frequency of LINE-1 hypomethylation and of CIN, and they were associated with a worse prognosis. EO-MSS were a genetically and epigenetically heterogeneous group of CRCs. Like LS-MSI, some EO-MSS displayed low rates of DNA hypo- or hypermethylation and frequent G:A transitions in theKRAS gene, suggesting that a genetic syndrome might still be unrevealed in these patients. By contrast, some EO-MSS showed similar features to those observed in S-MSS, such as LINE-1 hypomethylation, CIN, andTP53 deletion. In all four classes, hypermethylation ofESR1, GATA5, andWT1 was very common. Conclusions Aberrant DNA methylation analysis allows the identification of different subsets of CRCs. This study confirms the potential utility of methylation tests for early detection of CRC and suggests that LINE-1 hypomethylation may be a useful prognostic marker in both sporadic and inherited CRCs.